Integrated Weed Management in Maize (Zea mays L.) for Sustainable Productivity and Profitability of Maize-Wheat Cropping System in Southern Rajasthan - Hargilas, (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during two consecutive years of 2010−2011 and 2011−2012 to identify the most effective integrated weed management (IWM) practice for enhancing the production and productivity of maize-wheat cropping system. The treatments included pre-emergence herbicides, PE (Atrazine, metribuzin and oxyfluorfen) with and without hoeing, post-emergence herbicides, PoE (2,4-D), and smother crop (two rows of cowpea) simultaneously raised and mulched at 25 days after sowing (DAS) with weedy and weed-free check. The study found that the maximum maize grain yield of 5837 kg ha-1 occurred in the weed-free plot which was at par with the yield obtained from the maize+cowpea (raised as smothering crop and mulched at 25 DAS). Three treatments demonstrated increased grain yield of maize 73.04, 77.12 and 76.65% under mean of PE, PE+PoE and PE+one hoeing over weedy check, respectively. Furthermore, the treatments provided not only effective smothering-effects on weeds, but also significantly higher-yields in the succeeding wheat crop (5684 kg ha-1) under maize-wheat rotation. The highest benefit to cost (B: C) ratio was 2.69 with system productivity 11919 kg ha-1 when weed control in maize was achieved by smothering and mulching effects of cowpea. The results indicated that inclusion of cowpea as smother crop in between maize rows and it mulched at 25 days after sowing (DAS) offers a promising, cost-effective and efficient system for weed management in maize and is also provided an eco-friendly approach against herbicides application for sustaining the maize-wheat cropping system.